Modern views on endometriosis surgery. Literature review - M.M. Chernyak; О.О. Korchynska (Publishing House TRILIST, 2021)
Endometriosis is a disease associated with the presence of tissue morphologically similar to the endometrium outside the uterine cavity and it is an important medical and social problem. Statistical analysis of the endometriosis prevalence is complicated by polymorphism of manifestations a gradual increase of symptoms and a long period of time from the first symptoms to diagnosis. Manifestations of endometriosis are chronic pain, algodismenorea, dyspareunia, decreased fertility. All these manifestations worsen the quality of life and do not allow a woman to realize her reproductive potential. The most common forms of endometriosis are superficial peritoneal endometriosis, endometrioid ovarian cysts and deep infiltrative endometriosis. Treatment tactics depends on the form and stage of disease, woman's age, presence or absence of reproductive plans, previous treatment. It is possible to use both medical and surgical methods of treatment. Surgical methods can be organ-preserving and radical. The optimal surgical approach should weigh the risks of the surgery itself and the likelihood of recurrence in the radicalism absence. Modern techniques of surgical intervention are considered as one of the main methods of endometriosis treatment. Severe forms of endometriosis are a serious challenge for the surgical team, as chronic inflammation and adhesions alter the normal pelvis anatomy. Such operations often require the involvement of surgeons, urologists and other specialists, and the decision about final operation scope is made during the operation. Endometriosis surgery aims at the maximum possible in each case, the removal of pathological foci, which leads to relief of pain and increase the likelihood of reproductive plans. This article describes the rational scope of surgical interventions and optimal strategies for the management of patients with various forms of endometriosis. The data of international researches of efficiency of various methods of surgical interventions, influence of degree of radicalism on a disease course, probability of recurrence and quality of patient's life are resulted.